2012
DOI: 10.1155/2012/953627
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic Syndrome among Postmenopausal Women in Gorgan

Abstract: Introduction. The present study aimed to assess the metabolic syndrome among postmenopausal women in Gorgan, Iran. Materials and Methods. The study was conducted on hundred postmenopausal women who were referred to the health centers in Gorgan. Metabolic syndrome was diagnosed using Adult Treatment Panel III (ATP III) guidelines. Results. The mean body mass index, waist circumference, hip, circumference waist-to-hip ratio, diastolic blood pressure, and triglyceride and fasting blood glucose levels were signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
31
6
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 45 publications
14
31
6
2
Order By: Relevance
“…The prevalence of metabolic syndrome is influenced by dissimilarities in genetic factors, age, gender, diet and physical activity [2]. Studies of Marjani et al indicated that metabolic syndrome is changed in different ethnic and age groups, different diseases and postmenopausal women [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Progranulin is known with different names such as granulin-epithelin precursor [17], proepithelin [18][19] and acrogranin [20].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of metabolic syndrome is influenced by dissimilarities in genetic factors, age, gender, diet and physical activity [2]. Studies of Marjani et al indicated that metabolic syndrome is changed in different ethnic and age groups, different diseases and postmenopausal women [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Progranulin is known with different names such as granulin-epithelin precursor [17], proepithelin [18][19] and acrogranin [20].…”
Section: Introductionmentioning
confidence: 99%
“…Este hecho podría explicarse por la pérdida del efecto protector cardiovascular de los estrógenos, existe un mayor acumulo de grasa visceral o abdominal que es la que se ha asociado a resistencia a la insulina, hipertensión y al propio síndrome metabólico (Marjani & Moghasemi, 2012). De hecho, la mortalidad por origen cardiovascular sigue siendo significativamente mayor en este grupo cuando se compara con controles no menopausicas (Rosamond et al, 2007).…”
Section: Discussionunclassified
“…The metabolic syndrome is another important health issue among postmenopausal women [3]. Studies from different parts of the world have revealed that the prevalence of the metabolic syndrome reaches as high as 41.5% among postmenopausal women [4,5].…”
Section: Original Papersmentioning
confidence: 99%